Preliminary Study of Ceiling Board from Composite Material of Rice Husk, Rice Husk Ash and Waste Paper - Ang, Peniel Soon Ern; Ibrahim, Abdul Hadi Izaan; Abdullah, Mohd Sufyan (Progress in Engineering Application and Technology, 2020)
In Malaysia, natural fibre always ended either in trash, burned away or only used for agriculture purposes and it is frequently causing problems in the process of disposal and thus contributing to the pollution environment. This research was aimed at reducing and recycling rice husk, rice husk ash and waste paper from our environment thereby reducing environmental pollution resulting from the disposal of these waste materials. In this research, composite ceiling board materials made from rice husk, rice husk ash and waste paper, as developed at the Universiti Tun Hussein Onn, Pagoh were investigated to determine their suitability for use in low-cost construction work. Four test were conducted to determine the properties of the ceiling board which is density test, moisture content test, water absorption test and sound absorption test. The results obtained showed that the sound absorption ranged between 0.033α and 0.893α; water absorption values of between 31.26% and 102.9%; moisture content values of between 4.87% and 9.98% as well as density values of 0.5071g/cm3 and 1.067g/cm3. These values obtained were compared with those of the previous study and conventional ceiling boards and it was observed that sample 3 obtained the optimum results